2012
DOI: 10.4318/tjg.2012.0415
|View full text |Cite
|
Sign up to set email alerts
|

Potential proteomic biomarkers in assessing liver fibrosis using SELDI-TOF MS

Abstract: Amaç: Kronik karaci¤er hastal›¤› olan olgularda karaci¤er dokusundaki fibrozis varl›¤›n›n ve miktar›n›n de¤erlendirilmesi; tedavi stratejisini, tedaviye yan›t› ve prognozu belirleyen en önemli etkendir. Bu çal›flman›n amac› karaci¤er fibrozisinin de¤erlendiril-mesinde proteomik analiz ile yeni biyolojik belirteçlerin araflt›r›lmas›d›r. Yöntem: Kronik karaci¤er hastal›¤› olan toplam 87 hasta (Metavir indeks ile, 17 F0, 30 F1, 6 F2, 9 F3 ve 21 F4) (using METAVIR index, 17 F0, 30 F1, 6 F2, 9 F3, and 21 F4 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Technical problems include selecting the best proteomics method for serum biomarker discovery [ 5 ]. Potential proteomic biomarkers can be notably determined through SELDI-TOF-MS [ 39 , 40 ]. SELDI-TOF-MS is a widely used technique for diagnostic biomarker discovery in plasma, serum, and tissue and has the ability to carry out screening and identification.…”
Section: Discussionmentioning
confidence: 99%
“…Technical problems include selecting the best proteomics method for serum biomarker discovery [ 5 ]. Potential proteomic biomarkers can be notably determined through SELDI-TOF-MS [ 39 , 40 ]. SELDI-TOF-MS is a widely used technique for diagnostic biomarker discovery in plasma, serum, and tissue and has the ability to carry out screening and identification.…”
Section: Discussionmentioning
confidence: 99%
“…They obtained a sensitivity of 80.0% for all LC patients and a specificity of 81.8% for all noncirrhotic cohorts. Bozdayi et al [15] provided similar results with a sensitivity of 83.3% and a specificity of 85.1%. However, establishment of serum peptide pattern for predicting HBV-induced LC from noncirrhotic cohorts remains challenging.…”
Section: Introductionmentioning
confidence: 66%
“…In limited studies published to date, these have been demonstrated to be highly predictive (AUROC >0.85) of fibrosis in hepatitis C, hepatitis B and NAFLD. 28 Recent advances in genomics and the advent of new efficient tools for large-scale analysis of gene expression have provided new insights into the knowledge and understanding of gene networks and regulatory pathways in various disease processes. 29 These methods include microarrays which can be used to analyse the expression of thousands of genes at a time.…”
Section: Future Developmentsmentioning
confidence: 99%